Microbial Toxins Methods and Protocols - Holst, Otto.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2011)
Interest in the field of microbial toxins is ever growing and spreading across a broad spectrum of scientific disciplines. In an effort to supplement the available reference texts on toxins, Microbial Toxins: Methods and Protocols includes protocols on mold fungus toxins, with some focus on aflatoxins. Intended to support a wide variety of researchers, Microbial Toxins: Methods and Protocols presents the reader with biological, chemical, physical, and medical approaches, as well as state-of-the-art research techniques. Divided into three convenient sections, this detailed volume covers bacterial protein toxins, endotoxins, and mold fungus toxins. Written in the highly successful Methods in Molecular Biology™ series format, chapters contain introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and notes on troubleshooting and avoiding known pitfalls.   Authoritative and accessible, Microbial Toxins: Methods and Protocols seeks to serve both professionals and novices with its well-honed methodologies in an effort to further our knowledge of this essential field.
Bacterial Protein Toxins -- Detection of Bacterial Protein Toxins by Solid Phase Magnetic Immunocapture and Mass Spectrometry. Sensitive and Rapid Detection of Cholera Toxin-Producing Vibrio cholerae using Loop-Mediated Isothermal Amplification. Ultra Sensitive Detection of Botulinum Neurotoxins and Anthrax Lethal Factor in Biological Samples by ALISSA. Examination of Bacillus anthracis Spores by Multiparameter Flow Cytometry. A Cell-Based Fluorescent Assay to Detect the Activity of Shiga Toxin and Other Toxins That Inhibit Protein Synthesis. Use of a Vero Cell-Based Fluorescent Assay to Assess Relative Toxicities of Shiga Toxin 2 Subtypes from Escherichia coli. Molecular Methods – Chip Assay and Quantitative Real-Time PCR – in Detecting Hepatotoxic Cyanobacteria. Endotoxins -- Capillary Electrophoresis Chips for Fingerprinting Endotoxin Chemotypes from Whole-Cell Lysates. Isolation of Smooth-Type Lipopolysaccharides to Electrophoretic Homogeneity. A Method for Unobtrusive Labeling of Lipopolysaccharides with Quantum Dots. Fluorescence-Based Methods to Assay Inhibitors of Lipopolysaccharide Synthesis. Micromethods for Lipid A Isolation and Structural Characterization. Two Efficient Methods for the Conjugation of Smooth-Form Lipopolysaccharides (LPS) with Probes Bearing Hydrazine or Amino Groups. I. LPS Activation with Cyanogen Bromide. Two Efficient Methods for the Conjugation of Smooth-Form Lipopolysaccharides (LPS) with Probes Bearing Hydrazine or Amino Groups. II. LPS Activation with a Cyanopyridinium Agent. Mold Fungus Toxins -- Extraction and Analysis of Fumonisins and Compounds Indicative of Fumonisin Exposure in Plant and Mammalian Tissues and Cultured Cells. Determination of Fumonisins B1 and B2 in Maize Food Products by a New Analytical Method Based on High-Performance Liquid Chromatography and Fluorometric Detection with Post-Column Derivatization. A Confirmatory Method for Aflatoxin M1 Determination in Milk Based on Immunoaffinity Clean-Up and High-Performance Liquid Chromatography with Fluorometric Detection. Simultanious Determination of Aflatoxins B1, B2, G1 and G2 in Foods and Feed Materials by High-Performance Liquid Chromatography with On-Line Photochemical Derivatization and Fluorescence Detection. Highly Sensitive PCR-Based Detection Specific to Aspergillus flavus.A Rapid Enzymatic Method for Aflatoxin B Detection.
Keywords: Microbiology; Bacteriology; Microbiology; Bacteriology